STRATEGI PENGEMBANGAN WISATA AIR TERJUN TEMBULUN BERASAP DI KABUPATEN INDRAGIRI HULU - Muhammad Sabda Ilham H; Abdul Sadad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study aims to determine the development strategy and to determine the factors that hinder the tourism development strategy of Tembulun Berasap waterfall by the local government and the community in Pejangki Village, Batang Cenaku District, Indragiri Hulu Regency. This research is a study that uses a qualitative methodology. This research is descriptive in nature, correctly describes the reality of the development strategy of the Tembulun Berasap waterfall in Indragiri Hulu Regency. Qualitative research aims to reveal certain social situations by describing the true reality. The results of this study are the strategy for developing Tembulun Berasap waterfall tourism by the local government and the community in Pejangki Village, Batang Cenaku District, Indragiri Hulu Regency, including: a) renewal of the objectives of implementing strategies that will be formulated, especially in the form of coaching, counseling, socialization, and assistance. funds for the development of facilities and infrastructure so that the Tembulun Berasap Waterfall tourism object can provide sustainable benefits, b) renewal of regional regulations governing the implementation of tourism object development and implementation of tourism programs that can attract visitors, as well as increasing the role of Regional Government Work Units c) tourism marketing development programs, tourism destination development programs, partnership development programs, creative economic development programs based on cultural arts and creative arts stage activities are implemented optimally. The factors inhibiting the tourism development strategy of Tembulun Berasap waterfall by the local government and the community in Pejangki Village, Batang Cenaku District, Indragiri Hulu Regency are: a) the lack of infrastructure and tourism support facilities is still lacking as well as the maintenance of existing facilities is not optimal so that the available facilities look slum and not well maintained, b) lack of professional management in systematic and planned management, c) lack of APBD funds that affect the implementation of the Tembulun Berasap Waterfall tourism development program and 4) bad behavior of the community and tourists who cannot maintain the cleanliness and beauty of the waterfall tourism object Smoky Wall. Keywords: Development, Strategy, Tembulun Berasap Waterfall